Description of premarital sexual behavior in high school students in Jabodetabek - Ananda Shafa Fadhilah; Aisyah Ramadhani Kamilia Jasmine; Marwa Zakia Habibillah; Mohammad Aldin Dhafa Pratama; Aries Yulianto (Institute of Computer Science (IOCS), 2023)
Talking openly about sexual behavior in adolescents is still a taboo thing to do, but it's actually not taboo to do, especially among high school students. Dating has become something that is commonly done by high school students nowadays, most high school students have engaged in sexual behavior when dating. A number of studies in cities in Indonesia have shown that high school students have engaged in premarital sexual behavior. On the other hand, Jabodetabek is the area with the most rapid progress. This research wants to know about premarital sexual behavior among high school students in Jabodetabek. The research was conducted using a descriptive research strategy with a survey design. The results of the study show that students in Jabodetabek engage in sexual behavior from low intimacy, namely touching (65%) to the highest intimacy, namely sexual intercourse (0.83%). It can be concluded that the sexual behavior of high school students in Jabodetabek occurs sequentially from low intimacy to high intimacy.